Association of decreased lymphatic vessel density with postoperative eyelid edema - Bokman, Christine L.; Yu, Roy P.; Davuluru, Shaili S.; Sudharshan, Rasika; Park, Kristen E.; Guo, Sarah; Li, Joy; Mehta, Preeya; Shen, Alice; Chang, Jessica R.; Wong, Alex K.; Hong, Young-Kwon; et al. (Frontiers in Ophthalmology, 2026)
PurposeWe sought to investigate whether variations in lymphatic morphology are associated with postoperative eyelid edema in patients who underwent upper eyelid blepharoplasty.MethodsThis was a prospective study in which nine upper eyelid skin samples were stained with Podoplanin to immunochemically mark lymphatic vessels. Lymphatic vessel area, density, and perimeter were calculated from averaging 38 slices across 3 cuts of eyelid skin. Corresponding postoperative patient photographs were graded by four physicians with a standardized postoperative edema grading scale that ranged from zero (no edema) to three (severe edema). Patients were classified as having clinically significant eyelid edema (CSEE) if they received an edema grade greater than zero 90 days postoperatively or a grade of three at any time point.ResultsAnti-podoplanin staining demonstrated that there was significantly lower lymphatic vessel density among patients with severe edema (8.00 ± 1.67 vessels/mm2) compared to patients with mild or no edema (12.14 ± 1.93 vessels/mm2, p < 0.05). Lymphatic vessel area and perimeter did not reveal any significant associations with postoperative edema grades.ConclusionsIn patients undergoing an upper eyelid blepharoplasty, severe postoperative swelling was significantly associated with lower lymphatic vessel density, but not with lymphatic vessel area or perimeter. These findings suggest that the lymphatic network of the eyelid could play a role in the degree of postoperative swelling.